Service inclusion for tourists with disabilities: scale development and validation - Awan, M.I. (Emerald Group Holdings Ltd., 2022)
Purpose: The purpose of this study is to develop a scale for measuring service inclusion for tourists with disabilities in tourism and hospitality services. Transformative service research serves as the basis for the conceptualization and dimensionality. Design/methodology/approach: To develop and purify the items as well as develop dimensions, standard scale development procedures were applied. Two studies were undertaken. In Study 1, the factorial structure of the service inclusion was constructed and confirmed using exploratory and confirmatory factor analysis. In Study 2, the field study was conducted to validate the scale. Findings: The study developed a new scale for measuring service inclusion. The results show that service inclusion is a higher-order construct with four dimensions, namely, enabling opportunity, offering choice, relieving suffering and fostering happiness. Furthermore, service inclusion has a significant effect on touristsâ well-being perception, which results in more favorable behavioral responses. The newly constructed scale is declared as valid and reliable by the study that examined it for nomological validity by examining the relationship between service inclusion and touristsâ perceptions of their well-being. Originality/value: To the best of the authorsâ knowledge, this study is the first to develop measurement scale for service inclusion in the tourism and hospitality industry. The scale is proven as reliable and valid and is well suitable for measuring service inclusion for tourists with physical disabilities. It has potential to use for other relevant service contexts. Â© 2022, Emerald Publishing Limited.